LGBT characters in soap operas of Rede Globo from 2014 to 2016: a reflection from the Queer Studies - Santos, Tarcyanie Cajueiro (2019)
The article seeks to reflect on the representation of LGBT characters in soap operas of RedeGlobo. For that, a survey of LGBT characters present in Globo TV telenovelas from 2014 to 2016 was carried out, a survey of the websites of Gshow and MemóriaGlobo, besides consulting sites about telenovelas and also the follow-up, when watching during or after of the exhibition period, through the Globo Play platform. The analysis is based on queer studies, especially Judith Butler's theory of performativity. The study concludes that the telenovela constructs its representations in a negotiated way: if on the one hand, it increases the visibility of LGBT characters; on the other hand, it keeps them within a heteronormative or asexual pattern. Still, it favors greater acceptance of the generalized and sexed identities that are outside the heterosexual matrix.